The role of dexamethasone in the modification of misonidazole pharmacokinetics. - Jones, D. H. (Nature Publishing Group, 1983)
A review of misonidazole pharmacokinetics in 83 consecutive patients treated for tumours other than glioma has shown that among patients not receiving enzyme-inducing agents the plasma elimination half life is lower in patients taking steroids. Such a difference is not seen if patients already taking enzyme inducers are given steroids. Five further patients with carcinoma of the lung, treated with radiation over a period of 3 weeks, have been studied in greater detail. Misonidazole, in oral dose of 1 gm-2, was given in conjunction with the first and last radiotherapy fractions, and dexamethasone, in a divided daily dose of 8 mg, was given throughout the radiation treatment, commencing after the first treatment. Misonidazole pharmacokinetics were studied at each administration. Following the dexamethasone treatment period there was a 25% reduction in misonidazole plasma elimination half life, a 24% reduction in plasma AUC0-00, and a 38% increase in 24 h urinary excretion (all changes being statistically significant--P less than 0.005). No changes were observed in the plasma AUC0-24 and urinary excretion of the major metabolite desmethylmisonidazole. Glomerular filtration rates in one patient, before and after treatment with dexamethasone, remained unchanged. These results suggest that the effect of dexamethasone on misonidazole kinetics is not related to an enhancement of demethylation.